A Cultural Approach to Understanding Publics and their Information Behaviors during COVID-19: Self-Construal and Identity Salience. Issue 1 (2nd January 2023) - Ni, Lan; Shen, Hongmei
ABSTRACT: Integrating the situational and cross-situational approaches to understanding publics, this study examined cultural antecedents (self-construal and political identity salience) to situational perceptions (problem recognition, involvement recognition, constraint recognition), situational motivation, and key information behavior regarding the COVID-19 pandemic. Results from an online survey (N = 556) showed that political identity salience and interdependent self-construal triggered publics' situational perceptions, which in turn activated their situational motivation and information forwarding behaviors. The study contributed to public research through examining important cultural influences on value-laden and polarized issues and revealing additional nuances in communicative activeness.